Evolution of Xanthomonas Gene Content: Gene Gain/Loss History and Species Divergence - Gu-lei JIN; Guo-qing ZHANG; Guan-lin XIE; Jun ZHU; Miao-miao LOU; Xue-ping ZHOU; Xiao-wei ZHANG; Guo-chang SUN; Bin LI; Bo ZHU (Journal of Integrative Agriculture)
Horizontal gene transfer (HGT) plays key roles in the evolution of pathogenetic bacteria, especially in pathogenetic associated genes. In this study, the evolutionary dynamics of Xanthomonas at species level were determined by the comparative analysis of the complete genomes of 15 Xanthomonas strains. A concatenated multiprotein phyletic pattern and a dataset with Xanthomonas clusters of orthologous genes were constructed. Mathematical extrapolation estimates that the core genome will reach a minimum of about 1547 genes while the pan-genome will increase up to 22624 genes when sequencing 1000 genomes. The HGT extent in this genus was assessed by using a Markov-based probabilistic method. The reconstructed gene gain/loss history, which contained several features consistent with biological observations, showed that nearly 60% of the Xanthomonas genes were acquired by HGT. A large fraction of variability was in the clade ancestor nodes and “leaves of the tree”. Coexpression analysis suggested that the pathogenic and metabolic variation between Xanthomonas oryzae pv. oryzicola and Xanthomonas oryzae pv. oryzae might due to recently-transferred genes. Our results strongly supported that the gene gain/loss may play an important role in divergence and pathogenicity variation of Xanthomonas species.